Clopidogrel Use Should Not Routinely Delay Surgical Hip Fracture Repair. Issue 3 (2016) - Hull, Jonathan
Abstract : Abstract: The prevalence of hip fractures continues to rise as the population ages. Delay in fixation greatly increases postoperative complications and mortality. The purpose of this review was to determine if surgical hip fracture repair should be delayed for patients taking clopidogrel. Delayed surgical fixation of hip fractures increases patient 1‐year mortality. Some institutions wait 5 days to perform operative hip repair in patients taking clopidogrel, in keeping with the drug manufacturer guidelines. The current literature was searched for evidence suggesting increased perioperative risks in this population. Five studies addressing this topic were selected for review. The prevalence of hip fractures is growing exponentially. This is increasing the burden on health care. Many health‐care systems not only are experiencing budget cuts but also must find a way to continue to treat the increasing number of patients. "Length of stay" (LOS) has become a phrase well known in today's medical model. LOS directly impacts insurance reimbursements and will become more important with bundled payments. Every facet of the health‐care industry is trying desperately to reduce LOS in facilities. This trend, in the setting of hip fracture, will actually improve patient outcomes. It is extremely important to repair hip fractures as soon as possible. If surgical repair of a hip fracture is delayed, then the risk of patient mortality increases. Many patients who present with a hip fracture are also taking the drug clopidogrel. In the past, the use of clopidogrel has delayed hip fracture repair by as much as 5 days. No current Level‐I evidence in support of this practice of delaying repair exists, to my knowledge. Evidence does suggest that there is no need to wait 5 days to repair hip fractures in the clopidogrel population. Many surgical disciplines, including vascular, are performing procedures within 48 hours after discontinuing clopidogrel.